Fish Biodiversity in Ain Al-Ghazala Lagoon - Amani Fitori,; Alia Salem, (AlQalam Journal of Medical and Applied Sciences, 2025)
Ain Al-Ghazala Lagoon, located along the northeastern Mediterranean coast of Libya, is a key coastal ecosystem with rich biodiversity. This study aims to assess the fish species composition and their ecological roles within the lagoon. Fish samples were collected in summer and winter of 2024, with the assistance of local fishermen, and analyzed based on their morphological characteristics. The findings revealed a diverse range of species from the class Actinopterygii, occupying various habitats, including brackish and rocky reef environments. Several species, such as Atherina boyeri and Mugil cephalus, serve as important prey for higher trophic-level predators, while apex predators like Epinephelus marginatus play a key role in maintaining the food web balance. Many species, including Dicentrarchus labrax and Sparus aurata, have significant economic value in regional fisheries and aquaculture. However, the lagoon also faces ecological threats from invasive Lessepsian species, such as Siganus luridus and Pterois miles, which disrupt local ecosystems and pose risks to biodiversity. The study underscores the need for effective management strategies to conserve the lagoon’s biodiversity and ensure sustainable fisheries. Further research is required to assess the impact of invasive species and to address the combined challenges of overfishing, climate change, and habitat degradation.